Polygon map of soil units with functional properties for Mexico (1:250000) - Delerce, Sylvain Jean (2018)
This 1:250000 soil map of Mexico is the result of a combination of three INEGI open-access datasets: •The Series II soil units’ vectorial map is a nationwide polygon map delineating the soil groups at scale 1:250 000. It uses the World Reference Base for Soil Resources (WRB) to classify soils, and holds 63794 polygons. •The Series I soil profiles data is a compendium of 9537 soil profiles collected between 1980 and 1998 all around Mexico. •The Series II soil profiles data is a compendium of another 4418 soil profiles collected between 2002 and 2006 in the whole country. It consists of a polygon map of 2257 soil units of which 1498 are characterized with 9 attributes of soil functional properties.